Exploring Diabetes Mellitus' Impact on Tuberculosis Outcomes: A Comprehensive Comparative Study - Adawiyah Putri Diana; Ronald Pratama Adiwinoto; Retno Budiarti; Soedarsono; Hanung Prasetya; Oki Nugraha Putra (Journal of Epidemiology and Public Health, 2025)
Background: Tuberculosis (TB) remains among the top ten global causes of mortality, with approximately 1.3 million deaths annually. Diabetes elevates the risk of active TB and treatment failure, potentially increasing drug-resistant TB (DR-TB). This study aimed to compare treatment success rates between TB patients with and without diabetes mellitus (DM) at Dr. Ramelan Central Naval Hospital, Surabaya.Subjects and Method: This cross-sectional study was conducted from January 2019 to December 2023 at Dr. Ramelan Central Naval Hospital Surabaya. A total of 158 patients with TB-DM and TB-NonDM were selected using total sampling. The independent variables were the Presence of Diabetes Mellitus in TB patients (TB-DM vs. Non-TB-DM). The dependent variable was the treatment success rate. The data were collected from patient medical records and analyzed using a chi-square test to compare treatment outcomes between TB-DM and TB-Non-DM patients.Results: The analysis included 158 medical records. Predominantly affecting those over 45 years, both TB-DM and TB-Non-DM patients commonly underwent six months of treatment, with success rates of 78% in TB-DM and 82.4% in TB-Non-DM cases. The chi-square test yielded a p-value of 0.511, indicating no significant difference in treatment success between the groups. However, older age and HIV-positive status were associated with lower odds of treatment success.Conclusion: Success rates were similar between the groups, showing no significant difference based on DM status. Despite similar success rates, older age and HIV-positive status were associated with lower odds of treatment success.